Pengaruh Free Float Dan Volatilitas Terhadap Likuiditas Saham Syariah Yang Terdaftar Indeks Saham JII70 - Akhirusanah, Lulu; Mujiyati, Mujiyati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to analyze the effect of free float and volatility on stock liquidity with stock return, size and stock price as control variables. This study employs quantitative methods, utilizing multiple linear regression analysis aided by SPSS software. The research population consists of companies included in the JII 70 stock index during the period of 2021 to 2022. The sampling approach employed in this study utilized a purposive sampling method to select 108 research samples. The results of the research analysis show that the free float and volatility variables before and after using the control variables have an effect on stock liquidity. Meanwhile, the test results show that the free float and volatility variables which are controlled individually with stock return, size and stock price have no effect on stock liquidity.